Information technology supporting healthcare and social care services: an e-marketplace case study - Cunha, Maria Manuela Cruz (2014)
The authors are developing a pilot project for a Municipality in the North of Portugal, envisaging the definition and implementation of an e-marketplace for healthcare and social services, in order to facilitate the interaction between healthcare and social services professionals and people with special needs (or their relatives). Based on the results of a survey on user needs analysis and expectations conducted in 2011, the paper discusses the relevance and interest of such platforms and the main drivers and motivations of the population for using such services, as well as which services would motivate citizens to use the platform. The results of the study will be used to select the products and services perceived to be the most desired by the potential users. The paper thus makes three main contributions: (1) the results of the study confirm the interest and the perceived potential of such a service, from the end-users perspective; (2) the findings support the advantage of expanding this pilot project to a full scale implementation; and (3) the performed analysis improves our understanding of the relations between the characteristics of the inquired population and the perceived interest in such platforms.